Influence of surface tension gradient on liquid circulation time in a draft tube airlift reactor - Albijanic, Boris; Chatterjee, S.; Subasinghe, Nimal; Asad, Mohammad W.A. (Elsevier, 2016)
This paper investigates the impact of surface tension gradient on liquid circulation time in a draft tube airlift reactor using dilute alcohol solutions. The experimental work proves the existence of three bubble regimes (Regime I: no bubbles in the downcomer; Regime II: a stagnant swarm of bubbles in the downcomer; Regime III: circulation of bubbles through the reactor) in the downcomer. A paired sample t-test also confirms the presence of these hydrodynamic regimes. The liquid circulation time results can be predicted from a proposed correlation which has two independent variables: surface tension gradient in dilute alcohol solutions as a variable representing the physical property of liquid phase, and superficial gas velocity as a hydrodynamic variable. The statistical evaluation quantifies the influence of each independent variable through its elimination from the proposed correlation. Additionally, the second approach compares the rate of change in the liquid circulation time with respect to the surface tension gradient and the superficial gas velocity. It was found that the superficial gas velocity was more significant variable than the surface tension gradient for all three hydrodynamic regimes. The influence of the surface tension gradient on the liquid circulation time was insignificant at lower superficial gas velocity due to a negligible amount of bubbles in the reactor. However, the opposite was true at higher superficial gas velocity. It is evident that in the draft tube airlift reactor environment, the effect of surface tension gradient on liquid circulation time largely depends on superficial gas velocity.